2002
DOI: 10.1080/003655902320248227
|View full text |Cite
|
Sign up to set email alerts
|

Alarm Treatment for Childhood Nocturnal Enuresis: An Investigation of Within-treatment Variables

Abstract: The success of alarm treatment is dependent on the child's ability to be aroused by the alarm. Interestingly, of those who successfully became dry, 72.2% slept throughout the night for >80% of nights that they were dry, suggesting that the mode of action of the enuresis alarm is more complex than was previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Monda (1995) showed that, of the 79 patients treated with alarm therapy 63% were continent at 6 months and 56% were dry at 12 months. In our study, the 72% initial success rate obtained by the participants is in accordance with previous results of Butler (2002, Fai -Ngo (2005) and Van Leerdam (2004) -65% on average. But as the relapse criterion was defined as more than one wet night per week after dryness was achieved our longterm data showed that relapse is the main problem of this therapy.…”
Section: Discussionsupporting
confidence: 81%
“…Monda (1995) showed that, of the 79 patients treated with alarm therapy 63% were continent at 6 months and 56% were dry at 12 months. In our study, the 72% initial success rate obtained by the participants is in accordance with previous results of Butler (2002, Fai -Ngo (2005) and Van Leerdam (2004) -65% on average. But as the relapse criterion was defined as more than one wet night per week after dryness was achieved our longterm data showed that relapse is the main problem of this therapy.…”
Section: Discussionsupporting
confidence: 81%
“…Some factors may affect the response to alarm treatment, especially those of a psychological nature, such as marital conflict, lack of motivation and parental punishment (13). The physiological aspects associated with a poor response to alarm treatment include the difficulty to wake up with the sound of the device (15). The literature concerning the impact of enuresis severity on the outcome of alarm treatment is contradictory, with both positive (13) and negative (16) impacts being reported.…”
Section: Introductionmentioning
confidence: 90%
“…* Two of the complete responders relapsed but fell into partial responders group Compared with previous reports from other populations, our interventions were less successful. Butler et al [20] recently reported complete remission in 54.5% and partial success in 12.1% of patients with alarm therapy for 16 weeks. The commonly reported response rates for desmopressin have varied from 61% to 93% [21,22,23,24,25,26].…”
Section: Discussionmentioning
confidence: 95%